Epidemiology and risk factors of peri‐implantitis: A systematic review - Dreyer, H.; Grischke, J.; Tiede, C.; Eberhard, J.; Schweitzer, A.; Toikkanen, S. E.; Glöckner, S.; Krause, G.; Stiesch, M. (Journal of periodontal research, 2018)
The purpose of this systematic review and meta‐analysis was to assess the prevalence, incidence and risk factors of peri‐implantitis in the current literature. An electronic search was performed to identify publications from January 1980 until March 2016 on 9 databases. The prevalence and incidence of peri‐implantitis were assessed in different subgroups of patients and the prevalences were adjusted for sample size (SSA) of studies. For 12 of 111 identified putative risk factors and risk indicators, forest plots were created. Heterogeneity analysis and random effect meta‐analysis were performed for selected potential risk factors of peri‐implantitis. The search retrieved 8357 potentially relevant studies. Fifty‐seven studies were included in the systematic review. Overall, the prevalence of peri‐implantitis on implant level ranged from 1.1% to 85.0% and the incidence from 0.4% within 3 years, to 43.9% within 5 years, respectively. The median prevalence of peri‐implantitis was 9.0% (SSA 10.9%) for regular participants of a prophylaxis program, 18.8% (SSA 8.8%) for patients without regular preventive maintenance, 11.0% (SSA 7.4%) for non‐smokers, 7.0% (SSA 7.0%) among patients representing the general population, 9.6% (SSA 9.6%) for patients provided with fixed partial dentures, 14.3% (SSA 9.8%) for subjects with a history of periodontitis, 26.0% (SSA 28.8%) for patients with implant function time ≥5 years and 21.2% (SSA 38.4%) for ≥10 years. On a medium and medium‐high level of evidence, smoking (effect summary OR 1.7, 95% CI 1.25‐2.3), diabetes mellitus (effect summary OR 2.5; 95% CI 1.4‐4.5), lack of prophylaxis and history or presence of periodontitis were identified as risk factors of peri‐implantitis. There is medium‐high evidence that patient’s age (effect summary OR 1.0, 95% CI 0.87‐1.16), gender and maxillary implants are not related to peri‐implantitis. Currently, there is no convincing or low evidence available that identifies osteoporosis, absence of keratinized mucosa, implant surface characteristics or edentulism as risk factors for peri‐implantitis. Based on the data analyzed in this systematic review, insufficient high‐quality evidence is available to the research question. Future studies of prospective, randomized and controlled type including sufficient sample sizes are needed. The application of consistent diagnostic criteria (eg, according to the latest definition by the European Workshop on Periodontology) is particularly important. Very few studies evaluated the incidence of peri‐implantitis; however, this study design may contribute to examine further the potential risk factors.